Laminate for thermal molding, molded article using same, and method for manufacturing molded article

By optimizing the combination of hard coating and protective film in the post-curing thermoforming laminate, the hard coating curing damage and pattern deterioration caused by thermoforming in the protective film state is solved, and a molded body with excellent fingerprint erasing and scratch resistance is achieved. It is suitable for mobile devices such as smartphones, laptops and front panels of vehicle-mounted displays.

CN120344392APending Publication Date: 2025-07-18MITSUBISHI GAS CHEM CO INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380084793.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-14
Filing Date
2023-12-07
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

When the conventional post-curing thermoforming laminated body is subjected to a protective film, the curing of the hard coating layer will be affected, resulting in a decrease in thermoformability, and the pattern transfer and appearance of the protective film will be deteriorated, and it is difficult to realize a molded body with excellent fingerprint erasing properties.

Method used

By stacking the substrate layer, the uncured hard coating layer and the protective film in turn, the hard coating layer is cured after removing the protective film, ensuring that the surface free energy of the hard coating surface is less than 20.0 mJ/m2, and using a combination of polymer and inorganic oxide nanoparticles with (meth)acryloyl group, the adhesion surface contact angle of the protective film is optimized, and the fingerprint erasability and scratch resistance of the hard coating are achieved.

Benefits of technology

While thermoforming is performed in the protective film state, the free energy of the hard coat surface is reduced, fingerprint erasing and scratch resistance are improved, damage to the hard coat layer and foreign objects are avoided, and the excellent performance of the molded body is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005441481990000101
    Figure BDA0005441481990000101
  • Figure BDA0005441481990000102
    Figure BDA0005441481990000102
  • Figure BDA0005441481990000103
    Figure BDA0005441481990000103
Patent Text Reader

Abstract

According to one embodiment, the present invention provides a laminate for post-curing thermoforming in which a substrate layer, an uncured hard coat layer, and a protective film are laminated in this order, the surface free energy of the surface of the hard coat layer being 20.0 mJ / m2 or less after the protective film is removed and the hard coat layer is cured, and the surface free energy of the surface of the hard coat layer being 20.0 mJ / m2 or less. The surface free energy is calculated according to the value of the average contact angle between the hard coating surface and water and the value of the average contact angle between the hard coating surface and cetane by a Kaelble-Uy method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate for post-curing thermoforming, a molded article using the laminate for post-curing thermoforming, and a method for manufacturing the molded article. Background Art

[0002] Hitherto, plastic household appliances, automotive products, etc. have generally been manufactured by coating plastic molded articles as needed. However, since this method has a large environmental load, various methods have been studied, typified by a method of insert molding a decorative film capable of thermoforming. In recent years, due to the increasing requirements for chemical resistance and scratch resistance of molded articles, the demand for a thermoforming laminate (for example, a film) with a hard coat has particularly increased. A thermoforming laminate with a hard coat is usually manufactured by applying a hard coat coating liquid on a substrate and then curing it (Patent Document 1).

[0003] In a normal hard coat film, there is a trade-off relationship between formability and chemical resistance and / or scratch resistance. That is, generally, if the formability is improved, the chemical resistance and / or scratch resistance will decrease; and if the chemical resistance and / or scratch resistance is improved, the formability will deteriorate. Therefore, in order to solve this problem, a post-curing type thermoforming laminate has been proposed in which a hard coat coating liquid is applied on a substrate and dried to form a hard coat, then it is formed in an uncured state, and after forming, the hard coat is cured by UV irradiation or the like.

[0004] In order to prevent scratches and foreign matter from biting in, there is also a case where a protective film is attached to the surface of the hard coat in the post-curing type thermoforming laminate. Since the biting in of foreign matter during the forming process significantly reduces the yield, it is necessary to perform the forming of the thermoforming laminate in a clean environment in a state where the protective film is attached.

[0005] However, in order to perform thermoforming, it is necessary to heat to a temperature above the glass transition temperature (Tg) of the substrate of the thermoforming laminate to soften the laminate. If heating is performed until the above temperature is reached in a state where a protective film is attached to an existing post-curing type thermoforming laminate, there will be a problem that the curing of the hard coat continues and the thermoformability is greatly impaired.

[0006] In addition, in an existing post-curing type thermoforming laminate, if thermoforming is performed in a state where a protective film is attached, there will also be problems such as transfer of the pattern of the protective film and deterioration of the appearance.

[0007] For these reasons, in existing post-curing thermoformable laminates, the protective film is usually peeled off before forming. To solve the above problems, a thermoformable laminate for thermoforming has been proposed that can be thermoformed with the protective film attached and can obtain a formed body with excellent thermoformability, chemical resistance, scratch resistance, etc. (Patent Document 2).

[0008] In addition, especially in mobile devices such as smartphones and laptops, and front panels of in-vehicle displays, etc., in addition to the above properties, fingerprint resistance is also desired. That is, if a formed body with fingerprint resistance can be manufactured using a laminate with a hard coat, it will be possible to provide products with added value such as less obvious fingerprints and easy erasure.

[0009] Prior Art Documents

[0010] Patent Documents

[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 2017-508828

[0012] Patent Document 2: International Publication No. 2021 / 157588 Summary of the Invention

[0013] Technical Problem to be Solved by the Invention

[0014] An object of the present invention is to provide a post-curing thermoformable laminate that can obtain a formed body with excellent fingerprint erasability.

[0015] Technical Solution for Solving the Technical Problem

[0016] As a result of intensive research, the inventors of the present invention have successfully obtained a post-curing thermoformable laminate as follows. After curing the hard coat, the surface free energy of the surface of the hard coat is 20.0 mJ / m 2 or less. Using such a thermoformable laminate, a formed body with excellent fingerprint erasability can be manufactured. The present invention is described as follows, for example.

[0017] [1] A post-curing thermoformable laminate, wherein the post-curing thermoformable laminate is formed by sequentially laminating a substrate layer, an uncured hard coat, and a protective film,

[0018] and after removing the protective film and curing the hard coat, the surface free energy of the surface of the hard coat is 20.0 mJ / m 2 or less. Hereinafter,

[0019] The above surface free energy is calculated according to the values of the average contact angle with water and the average contact angle with hexadecane on the surface of the hard coat by the Kaelble-Uy method.

[0020] [2] The laminate for post-curing thermoforming according to [1], wherein the adhesion surface of the protective film on the hard coat side has an average contact angle with water of 90° or more and an average contact angle with hexadecane of 8° or more before being adhered to the hard coat.

[0021] [3] The laminate for post-curing thermoforming according to [1] or [2], wherein the hard coat contains a polymer having a (meth)acryloyl group and inorganic oxide nanoparticles. When the total of the polymer and the nanoparticles is 100 parts by weight, the content of the polymer having a (meth)acryloyl group in the hard coat is 40 to 99 parts by weight, and the content of the inorganic oxide nanoparticles is 1 to 60 parts by weight.

[0022] [4] The laminate for post-curing thermoforming according to [3], wherein the polymer having a (meth)acryloyl group has a (meth)acrylic acid equivalent of 200 to 700 g / eq, and the inorganic oxide nanoparticles have an average particle diameter of 5 to 300 nm.

[0023] [5] The laminate for post-curing thermoforming according to any one of [3] to [4], wherein the hard coat further contains a leveling agent. When the total of the polymer and the nanoparticles contained in the uncured hard coat is 100 parts by weight, the content of the leveling agent is 0.001 to 10 parts by weight.

[0024] [6] The laminate for post-curing thermoforming according to [5], wherein the leveling agent is a fluorine-based additive.

[0025] [6-1] The laminate for post-curing thermoforming according to any one of [3] to [6], wherein the hard coat further contains a photoinitiator. When the total of the polymer and the nanoparticles contained in the uncured hard coat is 100 parts by weight, the content of the photoinitiator is 1 to 6 parts by weight.

[0026] [7] The laminate for post-curing thermoforming according to any one of [3] to [6-1], wherein the hard coat further contains a light stabilizer. When the total of the polymer and the nanoparticles contained in the uncured hard coat is 100 parts by weight, the content of the light stabilizer is 0.1 to 10 parts by weight.

[0027] [8] The laminate for post-curing thermoforming according to any one of [1] to [7], wherein the nanoindentation hardness of the uncured hard coat at a temperature of 30°C is 200 N / mm 2 or more.

[0028] [9] The post-curing type thermoformable laminate according to any one of [1] to [8], wherein, after removing the above-mentioned protective film and curing the above-mentioned hard coat, when the surface of the hard coat is scratched 15 times back and forth under a pressure of steel wool of 100 gf / cm 2 the haze change (ΔH) before and after scratching of the above-mentioned hard coat is 3.0% or less,

[0029] and the above-mentioned haze change (ΔH) is evaluated in accordance with JIS K 7136:2000.

[0030]

[10] The post-curing type thermoformable laminate according to any one of [1] to [9], wherein the above-mentioned hard coat is an active energy ray curable layer.

[0031] [10-1] The post-curing type thermoformable laminate according to any one of [1] to

[10] , wherein the adhesion surface of the above-mentioned protective film on the hard coat side has an average contact angle with water of 90° or more and an average contact angle with hexadecane of 8° or more before being bonded to the hard coat.

[0032]

[11] A molded article, wherein the molded article is obtained by curing the uncured hard coat in a molding intermediate formed by molding the post-curing type thermoformable laminate according to any one of [1] to [10-1].

[0033]

[12] A method for manufacturing a molded article, which includes:

[0034] a step of thermoforming the post-curing type thermoformable laminate according to any one of [1] to [10-1];

[0035] a step of removing the protective film from the post-curing type thermoformable laminate obtained by the above-mentioned thermoforming; and

[0036] a step of curing the hard coat exposed on the surface by removing the protective film.

[0037]

[13] The method for manufacturing a molded article according to

[12] , wherein the above-mentioned thermoforming is performed by insert molding.

[0038] Advantages of the Invention

[0039] According to the present invention, it is possible to provide a post-curing type thermoformable laminate capable of obtaining a molded article with excellent fingerprint erasability. Brief Description of the Drawings

[0040] Figure 1 It is a cross-sectional view showing an example of the thermoformable laminate of the embodiment of the present invention. Detailed Description of the Embodiment

[0041] Hereinafter, specific embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0042] According to one embodiment of the present invention, the post-curing thermoforming laminate of the present invention is formed by sequentially laminating an uncured hard coat and a protective film. After removing the protective film and curing the hard coat, the surface free energy of the hard coat is 20.0 mJ / m 2 Hereinafter. Among them, the surface free energy is calculated according to the Kaelble-Uy method based on the values of the average contact angle with water and the average contact angle with hexadecane on the surface of the cured hard coat.

[0043] The inventors of the present invention have successfully obtained a post-curing thermoforming laminate in which the surface free energy of the surface of the hard coat after thermoforming and curing is 20.0 mJ / m 2 Hereinafter. Moreover, it has been confirmed that the hard coat having such a surface free energy has excellent fingerprint erasability. Therefore, by forming the post-curing thermoforming laminate having such a hard coat, a molded article having excellent fingerprint erasability can be obtained. Among them, the fingerprint erasability refers to the ease of erasing (the ease of eliminating fingerprints) when wiping fingerprints attached to the surface of an object with a cloth or the like. The molded article with excellent fingerprint erasability can be applied to various household appliances, in-vehicle devices, automotive interior parts, etc., represented by mobile devices such as smart phones and laptop computers and the front panels of in-vehicle displays.

[0044] The inventors have considered various factors for controlling the surface free energy of the hard coat within the above range. For example, the inventors believe that the fluorine-based leveling agent contained in the hard coat composition can affect the surface free energy of the hard coat. That is, the inventors believe that the presence of fluorine components in the fluorine-based leveling agent on the surface of the hard coat is one of the factors for reducing the surface free energy of the hard coat.

[0045] In addition, the inventors believe that the material of the protective film for protecting the surface of the hard coat also affects the fingerprint erasability of the surface of the hard coat. According to one embodiment of the present invention, the average contact angle of the adhesion surface of the protective film on the hard coat side with water is 90° or more, and the average contact angle with hexadecane is 8° or more before being bonded to the hard coat. The smaller the value of the average contact angle of the adhesion surface of the protective film with hexadecane, the easier it is to adhere to the hard coat, and the more likely the adhesive paste component will remain on the hard coat when the protective film is peeled off. As a result, the fingerprint erasability of the surface of the hard coat deteriorates. Therefore, by using a protective film with an average contact angle with hexadecane above a certain value, it can be cleanly peeled off from the hard coat, further improving the fingerprint erasability of the surface of the hard coat.

[0046] Hereinafter, each component, manufacturing method, physical properties, uses, etc. of the post-curing thermoforming laminate according to the embodiment of the present invention will be described in detail.

[0047] [1] Laminated body for thermoforming

[0048] The laminated body for thermoforming according to an embodiment of the present invention includes (a) a base material layer, (b) a curable (uncured) hard coat, and (c) a protective film, which are laminated in the order of (a) the base material layer, (b) the hard coat, and (c) the protective film. That is, in the laminated body for thermoforming according to the embodiment of the present invention, the (a) base material layer is laminated on one surface of the (b) hard coat, and the (c) protective film is laminated on the other surface of the (b) hard coat. Moreover, the laminated body according to the embodiment of the present invention may further include layers other than the above (a) to (c), and each of the layers (a) to (c) may also have multiple layers.

[0049] Figure 1 It is a cross-sectional view showing an example of the laminated body for thermoforming according to the embodiment of the present invention. In Figure 1 , the laminated body 10 has the following structure: a hard coat 16 is laminated on a base material layer (for example, a base material layer including a polymethyl methacrylate layer (PMMA resin layer) 20 and a polycarbonate layer (PC resin layer) 22), and a protective film 12 is further laminated thereon. That is, the surface of the hard coat 16 is protected by the protective film 12. When the base material layer includes two or more layers as described above, its configuration is not particularly limited.

[0050] The laminated body for thermoforming according to the embodiment of the present invention is a post-curing type. Therefore, the laminated body for thermoforming according to the embodiment of the present invention has an uncured hard coat and can also perform a forming process in a state where the hard coat is uncured. When performing the forming process in a state where the hard coat is uncured, specifically, after the laminated body for thermoforming is formed into a desired shape and the protective film is peeled off, the hard coat exposed on the surface can be cured. Although it is also possible to perform the forming after peeling off the protective film, as described later, according to the embodiment of the present invention, the forming can be performed in a state where the protective film is attached. The curing means of the hard coat depends on the material of the hard coat, and examples thereof include curing using active energy rays or heat. Conventionally, if the forming is performed after curing the hard coat, there is a problem that fine cracks are generated in the hard coat, while if a post-curing type laminated body for thermoforming is used to perform the forming in a state where the hard coat is uncured, such problems do not occur. In addition, the laminated body for thermoforming according to the embodiment of the present invention can be smoothly formed in a state where the protective film is attached. Therefore, damage to the hard coat and biting of foreign substances during forming can be prevented.

[0051] Hereinafter, each layer of the laminate for thermoforming according to the embodiments of the present invention will be described in turn. In this specification, the liquid mixture for coating the hard coat on the substrate layer is referred to as "hard coat composition", the state after the hard coat composition is coated on the substrate layer and dried and before curing is referred to as "uncured hard coat", and the state after the hard coat is cured by active energy rays, heat, etc. is referred to as "cured hard coat". In addition, the cured state includes a semi-cured state that is not completely cured.

[0052] [2] Substrate layer

[0053] The substrate layer is preferably laminated in such a manner as to be in contact with the surface on the opposite side to the protective film of the hard coat. However, it is not limited thereto, and other layers may be disposed between the substrate layer and the hard coat.

[0054] The substrate layer preferably contains a thermoplastic resin. The type of the thermoplastic resin is not particularly limited, and various resins such as polycarbonate (PC) resin, acrylic resins such as polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyimide (PI), cycloolefin copolymer (COC), resin containing norbornene, polyethersulfone, cellophane, and aromatic polyamide can be used. The substrate layer preferably contains at least the polycarbonate resin among the above thermoplastic resins, and more preferably contains an aromatic polycarbonate resin from the viewpoints of toughness and heat resistance.

[0055] The type of the polycarbonate resin is not particularly limited as long as the main chain of the molecule contains a carbonate bond "-[O-R-OCO]-" (R is an aliphatic group, an aromatic group, or a group containing both an aliphatic group and an aromatic group, and may be a straight-chain structure or a branched-chain structure). Among them, a polycarbonate resin having a bisphenol skeleton is preferred, and a bisphenol A type polycarbonate resin having a bisphenol A skeleton or a bisphenol C type polycarbonate resin having a bisphenol C skeleton is particularly preferred. As the polycarbonate resin, a mixture of a bisphenol A type polycarbonate resin and a bisphenol C type polycarbonate resin, or a copolymer of bisphenol A and bisphenol C may also be used. In order to improve the hardness of the substrate layer, a bisphenol C type polycarbonate resin (for example, a polycarbonate resin made of bisphenol C, a mixture of a bisphenol A type polycarbonate resin and a bisphenol C type polycarbonate resin, or a copolymer of bisphenol A and bisphenol C) is preferably used.

[0056] As the thermoplastic resin contained in the base material layer, an acrylic resin is also preferred. Specifically, examples include, but are not particularly limited to, polymethyl methacrylate (PMMA), homopolymers of various (meth)acrylates represented by methyl methacrylate (MMA), or copolymers of PMMA, MMA, and the monomers constituting them and one or more other monomers. In addition, a mixture of multiple resins can also be used. Among them, (meth)acrylates containing a cyclic alkyl structure with low birefringence, low hygroscopicity, and excellent heat resistance are preferred. Examples of such (meth)acrylates include, but are not limited to, ACRYPET (manufactured by Mitsubishi Rayon), Delpet (manufactured by Asahi Kasei Chemicals), and Parapet (manufactured by Kuraray), etc.

[0057] Moreover, the base material layer can be formed by multiple layers with different compositions. For example, a base material layer containing the above-mentioned polycarbonate resin layer and acrylic resin layer can be used. The base material layer with a multi-layer composition is not limited to a double-layer structure and can also be three layers or more. For example, when using a base material layer containing a polycarbonate resin layer and an acrylic resin layer, it is preferred to laminate a hard coat on the acrylic resin side. By laminating a hard coat capable of imparting fingerprint erasability on the acrylic resin layer with poor fingerprint erasability, a film with excellent fingerprint erasability can be obtained. By using a base material layer with a multi-layer structure containing a polycarbonate resin layer and an acrylic resin layer, not only can the surface hardness of the base material layer be improved, but also the thermoformability of the base material layer can be maintained.

[0058] The viscosity-average molecular weight of the thermoplastic resin contained in the base material layer is preferably 15,000 to 40,000, more preferably 20,000 to 35,000, and further preferably 22,500 to 25,000.

[0059] In addition, the base material layer can also contain additives as components other than the thermoplastic resin. Examples of additives include, for example, heat stabilizers, antioxidants, flame retardants, flame retardant aids, ultraviolet absorbers, mold release agents, colorants, etc., and the base material layer may contain one or more of them. Moreover, antistatic agents, fluorescent brighteners, antifogging agents, fluidity improvers, plasticizers, dispersants, antibacterial agents, etc. can also be added to the base material layer.

[0060] The content of the thermoplastic resin in the base material layer is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, relative to the mass of the base material layer. In addition, in the base material layer mainly composed of a polycarbonate resin, the proportion of the polycarbonate resin relative to the base material layer is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more. In the base material layer mainly composed of an acrylic resin, the proportion of the acrylic resin relative to the base material layer is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more. By setting the content of the thermoplastic resin within the above range, the fluidity during injection molding can often be further improved.

[0061] The thickness of the base material layer is preferably, but not particularly limited to, 0.10 mm to 1.0 mm. For example, the thickness of the base material layer is 0.15 mm to 0.80 mm, 0.18 mm to 0.60 mm, or 0.25 mm to 0.40 mm. By setting it within the above thickness range, a film with excellent formability and hardness can be achieved.

[0062] In the case where the base material layer is composed of multiple layers, either the thickness of each layer is within the above range, or the overall thickness of the base material layer is within the above range.

[0063] [2] Hard coat

[0064] The composition of the hard coat is not particularly limited as long as the surface free energy of the surface of the cured hard coat is 20.0 mJ / m 2 or less. The surface free energy is calculated by measuring the average contact angle with water and the average contact angle with hexadecane on the surface of the cured hard coat according to the Kaelble-Uy method. Since the average contact angles with water and hexadecane are measured values for the cured hard coat, for example, the thermoformed laminate according to the embodiment can be thermoformed arbitrarily, the protective film on the surface of the hard coat can be removed, and then the cured hard coat obtained by curing the hard coat can be measured. More specific methods for measuring the average contact angle and calculating the surface free energy are as described in the examples below. The surface free energy of the cured hard coat is preferably 19.0 mJ / m 2 or less, more preferably 18.0 mJ / m 2 or less, and can be, for example, 15.0 to 20.0 mJ / m 2 , 15.0 to 19.0 mJ / m 2 , or 15.0 to 18.0 mJ / m 2 .

[0065] The material of the hard coat is preferably, but not particularly limited to, including, for example, a radiation curable resin or a thermosetting resin. When the hard coat contains such a curable resin, it is preferable because the hard coat can be cured even without using a curing agent. The hard coat may also contain various additives for improving properties. Examples of such additives include nanoparticles, photoinitiators, leveling agents, light stabilizers, polymerization inhibitors, and the like.

[0066] (1) Curable resin

[0067] The hard coat preferably contains a radiation curable resin or a thermosetting resin, and more preferably contains a radiation curable resin. As the radiation curable resin, any resin having radiation curability can be used. Examples of the radiation curable resin include (meth)acrylate polymers. More specifically, epoxy (meth)acrylate polymers, urethane (meth)acrylate polymers, and polyester (meth)acrylate polymers can be mentioned. Particularly suitable is a polymer having a (meth)acryloyl group, such as a (meth)acrylate polymer having a (meth)acryloyl group. More specifically, an epoxy (meth)acrylate polymer having a (meth)acryloyl group, a urethane (meth)acrylate polymer having a (meth)acryloyl group, and a polyester (meth)acrylate polymer having a (meth)acryloyl group can be mentioned. The radiation curable resin can be easily obtained from various companies. Hereinafter, a polymer having a (meth)acryloyl group will also be referred to as a (meth)acryloyl polymer.

[0068] It should be noted that in this specification, (meth)acrylate means methacrylate and / or acrylate, and (meth)acryloyl means methacryloyl and / or acryloyl. Other similar notations are also interpreted in the above manner.

[0069] · Epoxy (meth)acrylate polymer

[0070] The radiation curable resin can be, for example, an epoxy (meth)acrylate polymer. Among them, an epoxy (meth)acrylate polymer having a (meth)acryloyl group is preferable. The synthesis of epoxy (meth)acrylate is shown, for example, by formula (1). Epoxy (meth)acrylate can be obtained by adding acrylic acid or methacrylic acid having an unsaturated bond to an epoxide.

[0071]

[0072] (In formula (1), R is an alkyl group having 1 to 12 carbon atoms or a hydrogen atom, and the alkyl group may be substituted with one or more substituents selected from an epoxy group, a hydroxyl group, an acryloyl group, and a methacryloyl group. R' is a methyl group or a hydrogen atom.)

[0073] Epoxy (meth)acrylate polymers can be obtained, for example, by copolymerizing (meth)acrylic acid with glycidyl (meth)acrylate to synthesize an epoxy resin having a (meth)acrylate backbone, and adding acrylic acid, methacrylic acid, etc. thereto. Its synthesis is shown, for example, by formula (2).

[0074]

[0075] As a preferred epoxy (meth)acrylate polymer, for example, a polymer having a repeating unit represented by the following formula (I) can be mentioned.

[0076]

[0077] In formula (I), m is an alkylene group having 1 to 4 carbon atoms or a single bond; n is an alkyl group having 1 to 4 carbon atoms or a hydrogen atom; p is a single bond or an alkylene group having 1 or 2 carbon atoms; q is an alkyl group having 1 to 12 carbon atoms which may have one or more substituents selected from an epoxy group, a hydroxyl group, an acryloyl group, and a methacryloyl group, or is a hydrogen atom.

[0078] In the above formula (I), preferably, m is an alkylene group having 1 or 2 carbon atoms; n is an alkyl group having 1 or 2 carbon atoms; p is a single bond or a methylene group; q is an alkyl group having 1 to 6 carbon atoms which may have one or more substituents selected from an epoxy group, a hydroxyl group, and an acryloyl group, or is a hydrogen atom. More preferably, m is a methylene group, n is a methyl group, p is a single bond, q is an alkyl group having 5 or less carbon atoms which may have one or more substituents selected from a methyl group or an epoxy group, or is an alkyl group having 8 or less carbon atoms which may have one or more substituents selected from a hydroxyl group and an acryloyl group.

[0079] As specific examples of the repeating unit represented by formula (I), the repeating units represented by the following formula (II-a), formula (II-b), and formula (II-c) can be mentioned.

[0080]

[0081] When the epoxy (meth)acrylate polymer contains the repeating units of formula (II-a), formula (II-b), and formula (II-c), based on the total molar amount of the repeating unit of formula (II-a), the repeating unit of formula (II-b), and the repeating unit of formula (II-c), the proportion of the repeating unit of formula (II-a) is preferably 30 to 85 mol%, more preferably 40 to 80 mol%; the repeating unit of formula (II-b) is preferably 5 to 30 mol%, more preferably 10 to 25 mol% based on the above total molar amount; further, the repeating unit of formula (II-c) is preferably 10 to 40 mol%, more preferably 10 to 35 mol% based on the above total molar amount.

[0082] Moreover, the molar ratio of the repeating unit of the above formula (II-a), the repeating unit of the formula (II-b), and the repeating unit of the formula (II-c) is preferably 4.5 to 5.5:1.5 to 2.5:2.5 to 3.5, for example, about 5:2:3.

[0083] ·Urethane (meth) acrylate polymer

[0084] The polymer having a (meth) acryloyl group may be a urethane (meth) acrylate polymer. Specifically, the urethane (meth) acrylate polymer described below can be cited. As a specific preferred example of the urethane (meth) acrylate polymer, a urethane (meth) acrylate polymer containing a structural unit derived from an isocyanate compound and a structural unit derived from a compound having a (meth) acryloyloxy group and a hydroxyl group can also be cited.

[0085] ·Isocyanate compound

[0086] As the isocyanate compound, for example, an aromatic isocyanate that may have an alkyl substituent (such as methyl) can be used. An aromatic isocyanate having 6 to 16 carbon atoms is preferred, an aromatic isocyanate having 7 to 14 carbon atoms is more preferred, and an aromatic isocyanate having 8 to 12 carbon atoms is particularly preferred.

[0087] Although the isocyanate compound is preferably an aromatic isocyanate, an aliphatic or alicyclic isocyanate can also be used.

[0088] Specific examples of the isocyanate compound include, for example, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, hydrogenated benzene dimethyl diisocyanate, benzene dimethyl diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, tetramethylbenzene dimethyl diisocyanate, isophorone diisocyanate, norbornene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, phenylene diisocyanate, lysine diisocyanate, lysine triisocyanate, naphthalene diisocyanate and other polyisocyanates, trimer compounds or tetramer compounds of these polyisocyanates, biuret type polyisocyanates, water-dispersible polyisocyanates (such as "Aquanate 100", "Aquanate 110", "Aquanate 200", "Aquanate 210", etc. manufactured by Nippon Polyurethane Industry Co., Ltd.), and reaction products of these polyisocyanates with polyols, etc.

[0089] Among these isocyanate compounds, diphenylmethane diisocyanate, toluene diisocyanate, naphthalene diisocyanate, trimethylolpropane (TMP) adduct of toluene diisocyanate, isocyanate body of toluene diisocyanate, TMP adduct of xylene diisocyanate, dicyclohexylmethane diisocyanate (H12MDI) represented by the following formula, isophorone diisocyanate (IPDI), xylylene diisocyanate (XDI), etc. are particularly preferred.

[0090]

[0091] · Acrylate compound

[0092] Examples of the acrylate compound for forming a urethane (meth)acrylate polymer having a molecular structure containing a cyclic skeleton include, for example, pentaerythritol triacrylate (PETA), dipentaerythritol pentaacrylate (DPPA), hydroxypropyl (meth)acrylate (hydroxypropyl acrylate; HPA), etc.

[0093] In addition, as the acrylate compound, a compound having a (meth)acryloyloxy group and a hydroxyl group, for example, a monofunctional (meth)acrylic acid-based compound having a hydroxyl group, can also be used.

[0094] Examples of the monofunctional (meth)acrylic acid-based compound having a hydroxyl group include monoesters of (meth)acrylic acid containing a hydroxyl group {for example, (meth)acrylic acid hydroxyalkyl esters [for example, (meth)acrylic acid 2-hydroxyethyl ester, (meth)acrylic acid 3-hydroxypropyl ester, (meth)acrylic acid 6-hydroxyhexyl ester, etc., (meth)acrylic acid hydroxy C2-20 alkyl esters, preferably (meth)acrylic acid hydroxy C2-12 alkyl esters, more preferably (meth)acrylic acid hydroxy C2-6 alkyl esters], monoesters of (meth)acrylic acid with polyalkylene glycols [for example, monoesters of (meth)acrylic acid with diethylene glycol, monoesters of (meth)acrylic acid with polyethylene glycol, etc., monoesters of (meth)acrylic acid with poly C2-4 alkylene glycols], monoesters of polyhydric alcohols having 3 or more hydroxyl groups [for example, monoesters of (meth)acrylic acid with glycerol, monoesters of (meth)acrylic acid with trimethylolpropane, etc., monoesters of (meth)acrylic acid with alkane polyols, monoesters of (meth)acrylic acid with polymers of alkane polyols such as monoesters of (meth)acrylic acid with diglycerol]}, N-hydroxyalkyl (meth)acrylamides (for example, N-hydroxymethyl (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, etc., N-hydroxy C1-4 alkyl (meth)acrylamides), adducts obtained by adding the hydroxyl group of these compounds (for example, (meth)acrylic acid hydroxyalkyl esters) to lactones (for example, C4-10 lactones such as ε-caprolactone) (for example, adducts obtained by adding about 1 to 5 moles of lactones), etc.

[0095] It should be noted that these acrylate compounds can be used alone or in combination of two or more.

[0096] As a specific preferred example of the compound for forming (meth)acryloyloxy, 2-hydroxy-3-phenoxypropyl acrylate can be cited.

[0097] Among the above, trimethylolpropane triacrylate (PETA), dipentaerythritol pentaacrylate (DPPA), and (meth)acryloxypropyl acrylate (acryloxypropyl acrylate, HPA) are particularly preferred.

[0098] Copolymer of isocyanate compound and acrylate compound

[0099] As specific preferred examples of the copolymer of an isocyanate compound and an acrylate compound, that is, a urethane (meth)acrylate polymer, copolymers of xylylene diisocyanate (XDI) and trimethylolpropane triacrylate (PETA), copolymers of XDI and dipentaerythritol pentaacrylate (DPPA), copolymers of dicyclohexylmethane diisocyanate (H12MDI) and PETA, copolymers of isophorone diisocyanate (IPDI) and PETA, copolymers of XDI and (meth)acryloxypropyl acrylate (HPA), etc. can be cited.

[0100] In addition, as a urethane (meth) acrylate polymer containing a cyclic skeleton molecular structure, in addition to the above-mentioned isocyanate compounds and acrylate compounds, copolymers using polyol compounds can also be cited. A polyol compound (polyol) is a compound having two or more hydroxyl groups in each molecule, and examples thereof include the following compounds. That is, as examples of polyol compounds, ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,5-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3-methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, neopentyl glycol, neopentyl glycol hydroxypivalate and other diols, these diols are polycaprolactone diols obtained by adding lactones such as ε-caprolactone, ester diols such as bis (2-hydroxyethyl) terephthalate, alkylene oxide adducts of bisphenol A, polyethylene glycol, polypropylene glycol, polybutylene glycol and other polyether diols, α-olefin epoxides such as propylene oxide and butylene oxide, monoglycidyl compounds such as Cardura E10 (synthetic highly branched saturated fatty acid glycidyl ester manufactured by Shell Chemical Company), glycerol, trimethylolpropane, trimethylolethane, diglycerol, triglycerol, 1,2,6-hexanetriol, pentaerythritol, dipentaerythritol, sorbitol, mannitol and other alcohols with three or more hydroxyl groups, these alcohols with three or more hydroxyl groups are polycaprolactone polyols obtained by adding lactones such as ε-caprolactone, alicyclic polyols such as 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated bisphenol A, hydrogenated bisphenol F, etc.

[0101] As the polyol structural unit, a urethane (meth) acrylate polymer containing a structural unit derived from tricyclodecane dimethanol (TCDDM) represented by the following formula is preferably used.

[0102]

[0103] Specific preferred examples of the urethane (meth) acrylate polymer containing a polyol structural unit include copolymers of tricyclodecane dimethanol (TCDDM), IPDI and PETA, copolymers of TCDDM, H12MDI and PETA, copolymers in which PETA is replaced with a copolymer using DPPA or a copolymer using PETA and also using DPPA, copolymers of TCDDM, xylylene diisocyanate (XDI) and hydroxypropyl (meth) acrylate (HPA), etc.

[0104] The urethane (meth)acrylate polymer containing a structural unit derived from a polyol compound in addition to an isocyanate compound and a compound having a (meth)acryloyloxy group and a hydroxyl group preferably contains at least a component represented by the following formula (i).

[0105] (A3)-O(OC)HN-A2-HN(OC)-O-A1-O-(CO)

[0106] NH-A2-NH-(CO)O-(A3)···(i)

[0107] In formula (i), A1 is an alkylene group derived from the above polyol compound; A2 are each independently an alkylene group derived from the above isocyanate compound; A3 are each independently an alkyl group derived from the above compound having a (meth)acryloyloxy group and a hydroxyl group.

[0108] Examples of the compound for forming A3 include 2-hydroxy-3-phenoxypropyl acrylate.

[0109] Other specific examples of the urethane (meth)acrylate polymer include the following compounds containing structural units derived from ethylene glycol, pentaerythritol triacrylate, and isophorone diisocyanate. In the following formula, n is an integer of 0 to 10, preferably an integer of 1 to 5, and more preferably an integer of 1 to 3.

[0110]

[0111] In the urethane (meth)acrylate polymer, the ratio of the structural unit derived from the compound having a (meth)acryloyloxy group and a hydroxyl group to the structural unit derived from the isocyanate compound is preferably 99:1 to 30:70 (weight ratio), more preferably 97:3 to 60:40, and further preferably 95:5 to 80:20.

[0112] (Urethane (meth)acrylate polymer containing acrylate)

[0113] Preferred specific examples of the urethane (meth)acrylate polymer include polymers containing a structural unit derived from urethane (meth)acrylate and a structural unit derived from (meth)acrylate. More preferred specific examples of such urethane (meth)acrylate polymers include polymers containing a structural unit derived from a hexafunctional urethane (meth)acrylate and a structural unit derived from a bifunctional (meth)acrylate.

[0114] (Hexafunctional) urethane acrylate

[0115] As described above, the urethane (meth)acrylate polymer preferably contains structural units derived from urethane (meth)acrylate, particularly hexafunctional urethane (meth)acrylate.

[0116] Preferred examples of the hexafunctional urethane acrylate include compounds represented by the following formulae, namely, reaction products of dicyclohexylmethane diisocyanate (H12MDI) and pentaerythritol triacrylate (PETA), reaction products of isophorone diisocyanate (IPDI) and PETA, etc. Specific examples of preferred products of these hexafunctional urethane acrylates include UN-3320HC (reaction product of H12MDI and PETA: manufactured by Negami Kogyo Co., Ltd.), CN-968 (reaction product of IPDI and PETA: manufactured by Sartomer Japan Co., Ltd.), CN-975 (manufactured by Sartomer Japan Co., Ltd.), etc.

[0117]

[0118] (Meth)acrylate (bifunctional (meth)acrylate, etc.)

[0119] The (meth)acrylate structural unit that can constitute the urethane (meth)acrylate polymer is preferably a structural unit derived from a compound having 4 to 20 carbon atoms that contains at least one (meth)acryloyloxy group and at least one vinyl ether group and may have substituents. The number of carbon atoms of the (meth)acrylate is preferably 6 to 18, more preferably 8 to 16. Examples of the substituent of the (meth)acrylate include an alkyl group, etc.

[0120] In addition, the (meth)acrylate is preferably a bifunctional (meth)acrylate.

[0121] As the (meth)acrylate, 2-(2-vinyloxyethoxy)ethyl (meth)acrylate (2-(2-vinyloxyethoxy)ethyl acrylate: VEEA) represented by the following formula is preferably used.

[0122]

[0123] (In the above formula, R is a hydrogen atom or a methyl group.)

[0124] In the urethane (meth)acrylate polymer, the ratio of the structural unit derived from urethane acrylate to the structural unit derived from (meth)acrylate is preferably 99:1 to 30:70 (weight ratio), more preferably 97:3 to 60:40, and further preferably 95:5 to 80:20.

[0125] (Fluorine-containing urethane (meth)acrylate polymer)

[0126] As the (meth)acrylate polymer, a fluorine-containing urethane acrylate polymer can be used. The fluorine-containing urethane acrylate polymer preferably contains at least the component represented by the following formula (ii).

[0127] (A3)-O(OC)HN-A2-HN(OC)-O-A1-O-(CO)NH-A2-NH-(CO)O-(A3)…(ii)

[0128] In the above formula (ii), A1 is preferably an alkylene group derived from a fluorine-containing diol having 8 or less carbon atoms which may have a substituent, and the number of carbon atoms is preferably 6 or less, for example, 1 to 4. Examples of the substituent contained in the alkylene group of A1 include an alkyl group and the like.

[0129] In the above formula (ii), A2s are independently an alkylene group derived from an aliphatic or alicyclic isocyanate having 4 to 20 carbon atoms which may have a substituent. The number of carbon atoms of A2 is preferably 6 to 16, more preferably 8 to 12. Examples of the substituent of the alkylene group of A2 include an alkyl group and the like.

[0130] In addition, as the alicyclic isocyanate forming A2, for example, isophorone diisocyanate represented by the following formula can be cited.

[0131]

[0132] In the above formula (ii), A3s are independently an alkyl group having 4 to 30 carbon atoms which contains at least one (meth)acryloyloxy group and may further have a substituent. The number of carbon atoms of A3 is 6 to 20, more preferably 8 to 16. Examples of the substituent of the alkyl group of A3 include a branched alkyl group and the like. A3 preferably contains at least two (meth)acryloyloxy groups, and for example, may contain three (meth)acryloyloxy groups.

[0133] In addition, A3 is derived from, for example, pentaerythritol triacrylate represented by the following formula.

[0134]

[0135] As the fluorine-containing urethane acrylate polymer, a compound formed from the above respective compounds is preferred, and the fluorine-containing urethane acrylate contains, for example, a compound represented by the following formula (IV).

[0136]

[0137] · Polyester (meth)acrylate polymer

[0138] The polymer having a (meth)acryloyl group may be a polyester (meth)acrylate polymer. As the polyester (meth)acrylate polymer, examples thereof include polymers obtained by a dehydration condensation reaction of (meth)acrylic acid, polycarboxylic acid (anhydride) and polyol. As the polycarboxylic acid (anhydride) used for such dehydration condensation reaction, examples thereof include succinic acid (anhydride), adipic acid, maleic acid (anhydride), itaconic acid (anhydride), trimellitic acid (anhydride), pyromellitic acid (anhydride), hexahydrophthalic acid (anhydride), phthalic acid (anhydride), isophthalic acid, terephthalic acid, etc. In addition, as the polyol used for the dehydration condensation reaction, examples thereof include 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, dimethylolheptane, dimethylolpropionic acid, dimethylolbutyric acid, trimethylolpropane, bis(trimethylol)propane, pentaerythritol, dipentaerythritol, etc.

[0139] As the polyester (meth)acrylate polymer, specific examples thereof include ARONIX M-6100, ARONIX M-7100, ARONIX M-8030, ARONIX M-8060, ARONIX M-8530, ARONIX M-8050 (the above are the trade names of polyester (meth)acrylate oligomers manufactured by Toagosei Co., Ltd.), Laromer PE44F, Laromer LR8907, LaromerPE55F, LaromerPE46T, Laromer LR8800 (the above are the trade names of polyester (meth)acrylate oligomers manufactured by BASF Corporation), Ebecryl 80, Ebecryl 657, Ebecryl 800, Ebecryl 450, Ebecryl 1830, Ebecryl584 (the above are the trade names of polyester (meth)acrylate oligomers manufactured by Daicel U.C.B. Ltd.), PHOTOMERRCC13-429, PHOTOMER 5018 (the above are the trade names of polyester (meth)acrylate oligomers manufactured by Sannopco Ltd.), etc.

[0140] · Other active energy ray curable resins

[0141] As the active energy ray curable resin, (meth)acrylate polymers other than the above may also be used, for example, (meth)acrylate polymers containing no (meth)acryloyl group, or (meth)acrylate polymers containing no (meth)acrylate skeleton, etc.

[0142] In addition, as the active energy ray curable resin, compounds other than (meth)acrylate compounds may also be used, for example, epoxy compounds, oxetane compounds, etc.

[0143] The resin contained in the hard coat may be one kind or two or more kinds. When the total of the resin and the nanoparticles is 100 parts by weight, the content of the resin in the hard coat is preferably 40 to 99 parts by weight, more preferably 50 to 95 parts by weight, and further preferably 60 to 90 parts by weight.

[0144] When using a polymer having a (meth)acryloyl group, preferably a (meth)acrylate polymer having a (meth)acryloyl group, as the active energy ray-curable resin, the polymer preferably has a (meth)acrylic acid equivalent of 200 to 700 g / eq. The (meth)acrylic acid equivalent of the polymer having a (meth)acryloyl group is more preferably 250 to 700 g / eq, further preferably 300 to 600 g / eq, and particularly preferably 360 to 550 g / eq. Here, the (meth)acrylic acid equivalent (g / eq) means the molecular weight per (meth)acryloyl group defined by [molecular weight / (number of (meth)acryloyl groups)]. For example, when using a polymer having a (meth)acrylic acid equivalent of 250 to 700 g / eq, a hard coat excellent not only in fingerprint erasability but also in scratch resistance can be obtained.

[0145] In addition, the (meth)acrylate polymer as the active energy ray-curable resin preferably has a weight-average molecular weight of 5000 to 200000. The weight-average molecular weight of the (meth)acrylate polymer is preferably 10000 to 150000, more preferably 15000 to 100000, and further preferably 20000 to 50000.

[0146] The weight-average molecular weight can be measured according to the description in paragraphs

[0061] to

[0064] of Japanese Patent Application Laid-Open No. 2007-179018. The details of the measurement method are as follows.

[0147] [Table 1]

[0148] Measurement conditions for weight-average molecular weight

[0149] Device Manufactured by Waters Corporation [Aliance] Chromatographic column Manufactured by Showa Denko [Shodex K-805L] (2 pieces) Detector UV detector: 254 nm Eluent Chloroform

[0150] That is, first, a standard curve showing the relationship between the elution time and the polymer molecular weight is prepared by the universal calibration method using polystyrene as the standard polymer. Then, the elution curve (chromatogram) of the (meth)acrylate polymer is measured under the same conditions as those of the above standard curve. Further, the weight-average molecular weight (Mw) is calculated based on the elution time (molecular weight) of polycarbonate and the peak area (number of molecules) at that elution time. The weight-average molecular weight is represented by the following formula (A), where Ni is the number of molecules having a molecular weight Mi.

[0151] Mw = ∑(NiMi 2 ) / ∑(NiMi) ···· (A)

[0152] The properties such as the surface dryness (tack free) before curing and scratch resistance after curing of the hard coat containing the (meth)acrylate polymer having the above (meth)acrylic acid equivalent and weight average molecular weight are good, and the curing and polymerization reactions can also proceed smoothly. In addition, by using a polymer having a (meth)acryloyl group in the hard coat, the surface dryness (anti-tack property) becomes good, and even when thermoforming is carried out in a state where a protective film is attached, the deterioration of the appearance can be suppressed. This is because the protective film is easily peeled off from the thermoformed laminate. It should be noted that the polymer having a (meth)acryloyl group is commercially available and can be easily obtained. For example, it can be obtained from Dainippon Ink and Chemicals, Incorporated, Kyoeisha Chemical Co., Ltd., DSP Gokyo Foods & Chemicals Co., Ltd., etc.

[0153] (2) Polyfunctional acrylate compound

[0154] The hard coat may contain a pentaerythritol-based polyfunctional acrylate compound. As the polyfunctional acrylate compound having a plurality of acrylate groups, preferably three or more acrylate groups, for example, pentaerythritol tetraacrylate and dipentaerythritol hexaacrylate represented by the following formulas (3) and (4) can be cited. In addition, pentaerythritol triacrylate etc. can also be used.

[0155]

[0156] When the total of the curable resin and the polyfunctional acrylate compound contained in the hard coat is 100 parts by weight, the content of the polyfunctional acrylate compound in the hard coat is preferably 70 parts by weight or less, more preferably 50 parts by weight or less, and further preferably 30 parts by weight or less. Thus, by adding the polyfunctional acrylate compound to the hard coat composition and reacting it with the acryloyl group, glycidyl group (epoxy group), hydroxyl group, etc. contained in the side chain of the resin (for example, (meth)acrylate polymer), a hard coat having higher scratch resistance can be formed.

[0157] (3) Nanoparticles

[0158] The hard coat may contain nanoparticles. Thereby, the scratch resistance and hardness of the hard coat can be improved. The nanoparticles can be either inorganic particles or organic particles, but inorganic nanoparticles are preferred, and inorganic oxide nanoparticles are more preferred. For example, metal oxide nanoparticles such as nano-silica, nano-alumina, nano-titanium dioxide, nano-zirconia, etc. can be used. And nano-diamond etc. can also be used.

[0159] The hard coat preferably contains silica particles as nanoparticles. The nanoparticles contained in the hard coat are preferably treated with a surface treatment agent. By surface treatment, inorganic nanoparticles can be dispersed in a hard coat composition, particularly in a resin (e.g., (meth)acrylate polymer), in a stable state.

[0160] As the surface treatment agent for treating the nanoparticles, a compound having a substituent capable of binding to the surface of the nanoparticles and a substituent having high compatibility with the components of the hard coat in which the nanoparticles are dispersed (e.g., (meth)acrylate polymer, polymer having a (meth)acryloyl group, etc.) is preferably used. For example, as the surface treatment agent, a silane compound, alcohol, amine, carboxylic acid, sulfonic acid, phosphonic acid, etc. can be used.

[0161] The inorganic nanoparticles preferably have a polymerizable group on the surface. The polymerizable group can be introduced by surface treatment of the inorganic nanoparticles. Specific examples of the polymerizable group include vinyl, (meth)acrylic group, free radical polymerizable group, etc.

[0162] The average particle size of the nanoparticles is preferably 5 to 300 nm, more preferably 5 to 200 nm, 5 to 180 nm, 5 to 90 nm, 10 to 80 nm, 20 to 70 nm, etc. It should be noted that the average particle size of the nanoparticles can be measured by observing the cross-section of the hard coat with an electron micrograph. For example, the average particle size can be obtained by taking a TEM image of the particle cross-section prepared by FIB processing, etc., measuring the diameter lengths of 50 observed particles, and calculating the average value. In the case where the particles are non-spherical, the average of the major axis and the minor axis is taken as the diameter of the particle. For example, when using nanoparticles having an average particle size of 5 to 200 nm, a hard coat having excellent fingerprint erasability and high nanoindentation hardness (uncured) can be obtained.

[0163] When the total of the resin and the nanoparticles contained in the uncured hard coat is set to 100 parts by weight, the hard coat preferably contains 1 to 60 parts by weight of nanoparticles, such as inorganic nanoparticles. More preferably, the hard coat composition contains 5 to 55 parts by weight of inorganic nanoparticles, and further preferably contains 10 to 50 parts by weight of inorganic nanoparticles.

[0164] (4) Levelling agent

[0165] The hard coat may also contain a leveling agent. Thereby, the leveling property, stain resistance, and abrasion resistance of the hard coat are improved. As the leveling agent, a fluorine-based additive or the like is preferably used. As the fluorine-based compound contained in the fluorine-based additive, for example, a compound having a perfluoropolyether bond can be cited. The fluorine-based additive can be synthesized by itself or commercially available products can be easily obtained. For example, the MEGAFAC RS series of DIC Corporation, the KY series of Shin-Etsu Chemical Co., Ltd., the OPTOOL series of Daikin Industries, Ltd., etc. can be used.

[0166] When the total of the resin and nanoparticles contained in the uncured hard coat is 100 parts by weight, the content of the leveling agent is preferably 0.001 to 10 parts by weight, more preferably 0.001 to 5 parts by weight, still more preferably 0.001 to 4 parts by weight, and particularly preferably 0.001 to 3 parts by weight.

[0167] (5) Photoinitiator

[0168] As described above, the resin contained in the hard coat is preferably an active energy ray-curable or thermosetting resin, more preferably an active energy ray-curable resin, and particularly preferably an ultraviolet-curable resin. Therefore, the hard coat may further contain a photoinitiator. As the photoinitiator, IRGACURE 184 (1-hydroxycyclohexyl phenyl ketone), IRGACURE 1173 (2-hydroxy-2-methyl-1-phenylpropan-1-one), IRGACURE TPO (2,4,6-trimethylbenzoyl diphenylphosphine oxide), IRGACURE 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide), EsacureONE (oligo(2-hydroxy-2-methyl-1-[4-(1-methylethenyl)phenyl]acetone)), etc. can be used. Among them, from the viewpoint of heat resistance, Esacure One or the like is preferably used as the photoinitiator.

[0169] When the total of the resin and nanoparticles contained in the uncured hard coat is 100 parts by weight, the content of the photoinitiator in the hard coat is preferably 1 to 6 parts by weight, more preferably 2 to 5 parts by weight, and particularly preferably 2 to 4 parts by weight.

[0170] (6) Light stabilizer

[0171] The hard coat may contain a light stabilizer. Thereby, deterioration of the resin caused by ultraviolet irradiation in the weather resistance test can be suppressed. As the light stabilizer, hindered amine compounds such as Tinuvin 123 (manufactured by BASF), Tinuvin 770DF (manufactured by BASF), Tinuvin 144 (manufactured by BASF), and LA-81 (manufactured by ADEKA) can be used.

[0172] When the total of the resin and the nanoparticles contained in the uncured hard coat is 100 parts by weight, the content of the light stabilizer in the hard coat is preferably 0.1 to 15 parts by weight, more preferably 0.1 to 7 parts by weight, and particularly preferably 0.3 to 5 parts by weight.

[0173] (7) Polymerization inhibitor

[0174] The hard coat may also contain a polymerization inhibitor. The polymerization inhibitor suppresses the polymerization of the curable resin caused by light or heat and improves the storage stability. As the polymerization inhibitor, for example, hydroxyaromatics, quinone compounds, nitrogen-containing compounds, sulfur-based compounds, etc. can be used.

[0175] More specifically, for example, phenothiazine, 2-hydroxy-1,4-naphthoquinone, N-isopropyl-N'-phenyl-p-phenylenediamine, 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl radical, 2-mercaptobenzimidazole, etc. can be used.

[0176] (8) Other additives

[0177] The hard coat may also contain other additives. For example, it may contain a heat stabilizer, an antioxidant, a flame retardant, a flame retardant aid, an ultraviolet absorber, a release agent, a colorant, etc. As long as it does not significantly impair the required physical properties, an antistatic agent, a fluorescent brightening agent, an antifogging agent, a fluidity improver, a plasticizer, a dispersant, an antibacterial agent, etc. can also be added to the hard coat.

[0178] The dilution solvent used for preparing the hard coat composition can be used to adjust the viscosity, and its use is not particularly limited as long as it is a non-polymerizable solvent. By using the dilution solvent, the hard coat composition can be easily coated on the substrate layer.

[0179] Examples of the dilution solvent include toluene, xylene, ethyl acetate, propyl acetate, butyl acetate, methyl cellosolve, ethyl cellosolve, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, methanol, ethanol, isopropyl alcohol, butanol, diacetone alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, hexane, heptane, octane, decane, dodecane, propylene glycol monomethyl ether, 3-methoxybutanol, etc.

[0180] <Manufacture of hard coat>

[0181] The hard coat is manufactured by coating a hard coat composition containing the materials as described above on a layer adjacent to the hard coat (for example, a substrate layer). For example, the hard coat composition can be prepared by mixing the respective materials and further stirring with a disperser.

[0182] As a coating method of the hard coat composition, methods such as using a bar coater, a gravure coater, a die coater, dip coating, and spraying can be cited. At this time, after applying the hard coat composition, it is dried at a specified temperature. As the drying temperature, it is preferably 30 to 150 °C, more preferably 60 to 130 °C. By drying at a temperature within the above range, organic solvents can be removed from the hard coat, and deformation of other layers due to heating can be prevented.

[0183] The film thickness of the hard coat is preferably but not particularly limited to 1 to 10 μm, more preferably 2 to 7 μm. By setting the film thickness within the above range, the performance required for the hard coat can be obtained, and problems are less likely to occur in terms of adhesion and formability.

[0184] <Physical properties of the hard coat>

[0185] (i) Fingerprint erasability

[0186] The hard coat according to the embodiment of the present invention has excellent fingerprint erasability. That is, even when fingerprints adhere to the surface of the cured hard coat, they can be easily wiped off with fewer strokes when wiped with a cloth. For example, when fingerprints adhere to the surface of the cured hard coat and are wiped with a cloth, they can be erased within 5 strokes or less, preferably 4 strokes or less. Such characteristics are particularly required in fields such as mobile devices such as smartphones and laptop computers, and household appliances, and can provide products with added value.

[0187] (ii) Scratch resistance

[0188] The hard coat according to the preferred embodiment of the present invention has excellent scratch resistance, that is, it has the characteristic of being less likely to be damaged. Specifically, after removing the protective film and curing the hard coat, when steel wool is reciprocally scratched on the surface of the hard coat under a pressure of 100 gf / cm 2 , the haze change (ΔH) before and after scratching of the hard coat is 3.0% or less. This haze change is preferably 2% or less, more preferably 1.5% or less, and particularly preferably 1.0% or less. The specific measurement method is as described in the following examples, and the haze change (ΔH) is evaluated according to JIS K 7136:2000.

[0189] (iii) Hardness

[0190] The hard coat according to the preferred embodiment of the present invention has a preferred nanoindentation hardness. That is, when measuring the nanoindentation hardness of the uncured hard coat, the nanoindentation hardness at 30 °C is 200 N / mm 2 or more, for example, 200 to 420 N / mm 2 . The nanoindentation hardness is preferably 220 N / mm 2Above (for example, 220 to 420 N / mm 2 ), more preferably 250 N / mm 2 Above (for example, 250 to 420 N / mm 2 ). By making the nanoindentation hardness of the uncured hard coat within the above range, the operability in the uncured state is good. It should be noted that the specific measurement method of nanoindentation hardness is as described in the following examples.

[0191] (iv) Average contact angle

[0192] On the surface of the cured hard coat, the average contact angle with water is preferably 90° or more, more preferably 100° or more, and particularly preferably 105° or more. In addition, the average contact angle with hexadecane is preferably 45° or more, more preferably 50° or more, and particularly preferably 55° or more. Since the average contact angle of the hard coat surface with water and the average contact angle with hexadecane are within such ranges, the surface free energy calculated from these values is within the desired range.

[0193] It should be noted that the above average contact angle with water and the average contact angle with hexadecane are measured in the same manner as the average contact angle of the protective film described in the following examples.

[0194] [3] Protective film

[0195] To prevent damage to the surface of the hard coat during processes such as molding, a protective film is disposed on the surface of the hard coat. The protective film is adhered to the surface of the hard coat, for example, after coating a hard coat composition on a substrate layer and drying. The surface in contact with the hard coat of the protective film is preferably an adhesive surface having an appropriate adhesive strength (adhesion force) so as to adhere to the surface of the hard coat. The composition of the protective film is not particularly limited, and a single-layer film having only an adhesive layer or a double-layer structure film having a substrate and an adhesive layer is preferred. In the double-layer structure protective film, the adhesive surface of the adhesive layer is laminated on the hard coat in contact with the hard coat. The protective film may also be a multilayer structure further including layers other than the above-mentioned substrate and adhesive layer. In addition, the protective film may be a single-layer structure, and even in the case of a single-layer structure protective film, the adhesive surface on the hard coat side surface has an appropriate adhesive strength.

[0196] When the protective film has a substrate, the substrate preferably contains a thermoplastic resin, more preferably a polyolefin resin. Examples of the polyolefin resin contained in the protective film include, for example, polyethylene, polypropylene, etc., and may be a homopolymer or a copolymer. Among the polyolefin resins, polyethylene is also preferred.

[0197] As the polyethylene, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), etc. can be used, and low density polyethylene is preferred.

[0198] In addition, as the polyolefin copolymer, a copolymer formed from ethylene or propylene and a monomer capable of copolymerizing with them can be used. As the monomer capable of copolymerizing with ethylene or propylene, for example, α-olefins, styrenes, dienes, cyclic compounds, compounds containing an oxygen atom, etc. can be cited.

[0199] As the α-olefin, 1-butene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. can be cited. As the styrene, styrene, 4-methylstyrene, 4-dimethylaminostyrene, etc. can be cited. As the diene, 1,3-butadiene, 1,5-hexadiene, 1,4-hexadiene, 1,7-octadiene, etc. can be cited. As the cyclic compound, norbornene, cyclopentene, etc. can be cited. As the compound containing an oxygen atom, hexenol, hexenoic acid, methyl octanoate, etc. can be cited. These monomers capable of copolymerizing can be used alone or in combination of two or more. In addition, it can also be a copolymer of ethylene and propylene.

[0200] In addition, the copolymer can also be any one of alternating copolymerization, random copolymerization, and block copolymerization.

[0201] The polyolefin resin contained in the base material of the protective film can also contain a modified polyolefin resin modified with a small amount of carboxyl group-containing monomers such as acrylic acid, maleic acid, methacrylic acid, maleic anhydride, fumaric acid, itaconic acid, etc. The modification can generally be achieved by copolymerization or graft modification.

[0202] The content of the thermoplastic resin (such as polyolefin resin) of the base material of the protective film relative to the total weight of the base material is preferably 80% by weight or more, more preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0203] The adhesive layer of the protective film preferably contains an elastomer or a thermoplastic resin. As the thermoplastic resin contained in the adhesive layer, polyolefin resins such as polyethylene and polypropylene can be cited, and it can be a homopolymer or a copolymer. Among the polyolefin resins, polyethylene is preferred.

[0204] The content of the elastomer or thermoplastic resin in the adhesive layer of the protective film relative to the total weight of the adhesive layer is preferably 80% by weight or more, more preferably 90% by weight or more, and particularly preferably 95% by weight or more.

[0205] The thickness of the protective film is preferably 10 to 100 μm, more preferably 20 to 80 μm. When the protective film is composed of two or more layers, the total thickness of each layer is preferably within the above range.

[0206] The adhesion surface of the protective film, that is, the adhesion surface on the hard coat side, preferably has an average contact angle with water of 90° or more and an average contact angle with hexadecane of 8° or more before being bonded to the hard coat. The above average contact angle with water is more preferably 95° or more, particularly preferably 97° or more, and even 100° or more. The above average contact angle with hexadecane is more preferably 10° or more, particularly preferably 15° or more, and even 16° or more. Since the average contact angle of the adhesion surface of the protective film with water and the average contact angle with hexadecane are within such a range, the protective film can be peeled off cleanly from the hard coat, and the adhesive component is not likely to remain on the hard coat, achieving further improvement in fingerprint erasability. It should be noted that the average contact angle with water and the average contact angle with hexadecane are measured as described in the following examples.

[0207] The value of the adhesion strength of the adhesion surface of the protective film relative to the surface of PMMA (polymethyl methacrylate resin layer) is preferably 5 (mN / 25 mm) or more and 5000 (mN / 25 mm) or less, more preferably 9 (mN / 25 mm) or more and 3000 (mN / 25 mm) or less.

[0208] [4] Method for manufacturing a thermoformable laminate

[0209] The thermoformable laminate according to the embodiment of the present invention is manufactured as follows. First, the material of the substrate layer is processed into a layer (sheet) by a conventional method to produce the substrate layer. For example, extrusion molding, casting molding, etc. can be used. As an example of extrusion molding, a method can be cited in which pellets, chips, or powders of a resin composition are melt-kneaded by an extruder and then extruded from a T-die head or the like, and the obtained semi-molten sheet is cooled and solidified in a state of being clamped by rollers to form a sheet.

[0210] Then, the hard coat composition obtained by mixing the above materials is coated on the outer surface of the obtained substrate layer having a single layer or multiple layers to form a hard coat.

[0211] Then, the above protective film is bonded onto the hard coat to manufacture a thermoformable laminate.

[0212] [5] Thermoforming of the laminate

[0213] The laminate for thermoforming according to the embodiment of the present invention is a post-curing type laminate. Therefore, the laminate for thermoforming according to the embodiment of the present invention can be formed in a state where the hard coat is not cured. Specifically, for example, after the laminate for thermoforming is formed into a desired shape (formed intermediate) and the protective film is peeled off, the hard coat exposed on the surface is cured. That is, according to one embodiment of the present invention, there is provided a formed body obtained by curing the uncured hard coat in the formed intermediate obtained by forming the post-curing type laminate for thermoforming. In addition, according to another embodiment of the present invention, there is provided a method for manufacturing a formed body, which includes a step of thermoforming the post-curing type laminate for thermoforming; a step of removing the protective film from the post-curing type laminate for thermoforming obtained by thermoforming; and a step of curing the hard coat exposed on the surface by removing the protective film. As a method for forming the laminate, any method can be used as long as it is a method for thermoforming a film. For example, the base material can be heated and formed by pneumatic pressure (pneumatic forming), formed under vacuum conditions (vacuum pneumatic forming), TOM forming, insert molding, etc. into a desired shape. Among them, from the perspective of environmental load, insert molding is preferably used.

[0214] The forming temperature is mainly determined by the Tg (glass transition temperature) of the thermoplastic resin contained in the base material layer. The forming temperature is preferably a temperature about 0 to 70 °C higher than the Tg of the thermoplastic resin contained in the base material layer, more preferably a temperature about 20 to 40 °C higher. For example, when the laminate has a base material layer containing a conventional bisphenol A type polycarbonate resin, it is optimal to perform forming in the range of 170 to 190 °C. Since the laminate for thermoforming according to the embodiment of the present invention is not easily subjected to a polymerization reaction (curing) of the hard coat at the above-mentioned temperature, it can be formed in a state where the protective film is attached. By performing a series of operations in a state where the protective film is attached, damage to the hard coat and biting of foreign matter during forming can be prevented.

[0215] [6]Manufacture of the formed body

[0216] As described above, when the hard coat is cured after removing the protective film from the laminate thermoformed into a specified shape, a formed body such as a cured film can be obtained. The technical means for curing the hard coat can be appropriately determined according to the composition of the hard coat. The obtained formed body can be used as, for example, a resin film laminate used in mobile devices, automotive interior parts, home appliances, etc.

[0217] Examples

[0218] The present invention will be described in detail below by way of examples, but the content of the present invention is not limited to these examples.

[0219] (Example 1)

[0220] 70 parts by weight of a UV-curable (meth)acryloyl polymer (SMP-360A manufactured by Kyoeisha Chemical Co., Ltd.) was mixed with 30 parts by weight of nano-silica particles (ORGANOSILICA SOL MEK-AC-4130Y manufactured by Nissan Chemical Industries, Ltd.: average particle size 40 - 50 nm). Then, 3 parts by weight of a photoinitiator ESACURE-ONE, 1 part by weight of a fluorine-based leveling agent RS-90, and 1 part by weight of a light stabilizer Tinuvin 123 were added. Then, cyclohexanone as a diluting solvent was added to make the solid content concentration reach 25% by weight and stirred to obtain a hard coat composition.

[0221] As a substrate layer, a double-layer product DF02U (manufactured by Mitsubishi Gas Chemical Company, Inc., thickness 0.254 mm) laminated with bisphenol A polycarbonate resin and PMMA resin was prepared. The hard coat composition obtained as described above was coated on the PMMA side of the substrate layer. The coating process was carried out using a #3.5 wire bar, and the coated hard coat composition was dried at a temperature of 130 °C for 3 minutes. Then, the coated surface was protected with a protective film to obtain a laminate for thermoforming. As the protective film, a laminated film (CF620A manufactured by Toray Film Processing Co., Ltd., thickness 30 μm) in which an elastomer (PE + rubber-based) adhesive layer was laminated on a PP (polypropylene) substrate was used. The thickness of the formed hard coat was about 4 μm.

[0222] (Example 2)

[0223] A laminate for thermoforming was produced in the same manner as in Example 1 except that a different protective film was used. The protective film used in Example 2 was a laminated film (MX-157-N manufactured by Matai Co., Ltd., Japan, thickness 30 μm) in which a PE (polyethylene) adhesive layer was laminated on a PP (polypropylene) substrate.

[0224] (Example 3)

[0225] A laminate for thermoforming was produced in the same manner as in Example 1 except that a different protective film was used. The protective film used in Example 3 was a laminated film (PAC-NA2-40 manufactured by Sun A.Kaken Company, Limited, thickness 40 μm) in which an elastomer (rubber-based) adhesive layer was laminated on a PE (polyethylene) substrate.

[0226] (Example 4)

[0227] A laminate for thermoforming was produced in the same manner as in Example 3 except that 0.5 part by weight of KY-1203 was used as the fluorine-based leveling agent.

[0228] (Example 5)

[0229] A laminate for thermoforming was produced in the same manner as in Example 3, except that 1.5 parts by weight of KY-1203 was used as a fluorine-based leveling agent.

[0230] (Example 6)

[0231] A laminate for thermoforming was produced in the same manner as in Example 3, except that SMP-550AP manufactured by Kyoeisha Chemical Co., Ltd. was used as an ultraviolet curable (meth)acryloyl polymer.

[0232] (Example 7)

[0233] A laminate for thermoforming was produced in the same manner as in Example 3, except that 50 parts by weight of nano-silica particles (manufactured by Nissan Chemical Industries, Ltd., silicone sol MEK-AC-4130Y) was mixed into 50 parts by weight of an ultraviolet curable (meth)acryloyl polymer (SMP-360A manufactured by Kyoeisha Chemical Co., Ltd.).

[0234] (Example 8)

[0235] A laminate for thermoforming was produced in the same manner as in Example 3, except that 30 parts by weight of K180SM-CL3 (manufactured by Admatechs Co., Ltd., Japan, average particle size: about 180 nm) was used as nano-silica particles.

[0236] (Example 9)

[0237] A laminate for thermoforming was produced in the same manner as in Example 1, except that a different protective film was used. The protective film used in Example 9 was a laminated film (MX-107N manufactured by Matsui Co., Ltd., Japan, thickness 30 μm) in which a PP (polypropylene) adhesive layer was laminated on a PP (polypropylene) substrate.

[0238] (Example 10)

[0239] A laminate for thermoforming was produced in the same manner as in Example 3, except that SMP-220A manufactured by Kyoeisha Chemical Co., Ltd. was used as an ultraviolet curable (meth)acryloyl polymer.

[0240] (Example 11)

[0241] A laminate for thermoforming was produced in the same manner as in Example 3, except that 30 parts by weight of 3SM-CL5 (manufactured by Admatechs Co., Ltd., Japan, average particle size: about 300 nm) was used as nano-silica particles.

[0242] (Comparative Example 1)

[0243] A thermoforming laminate was produced in the same manner as in Example 1, except that a different protective film was used. The protective film used in Comparative Example 1 was a laminated film (7A82, thickness 30 μm, manufactured by Toray Film Processing Co., Ltd.) in which a special PO (polyolefin) adhesive layer was laminated on a PP (polypropylene) substrate.

[0244] (Comparative Example 2)

[0245] A thermoforming laminate was produced in the same manner as in Example 3, except that 4 parts by weight of a silicone-based leveling agent BYK-UV3575 was used as a leveling agent.

[0246] (Comparative Example 3)

[0247] A thermoforming laminate was produced in the same manner as in Example 3, except that MAP-7000 manufactured by Negami Kogyo Co., Ltd. was used as the ultraviolet curable (meth)acryloyl polymer.

[0248] <Physical Property Evaluation>

[0249] Various physical property evaluations were performed on the thermoforming laminates prepared as described above, each component of the thermoforming laminates, and the cured hard coat as follows.

[0250] (1) Average Contact Angle of the Adhesive Surface of the Protective Film with Water

[0251] For the protective film before being adhered to the hard coat, the contact angle of its adhesive surface with water was measured. When measuring, a contact angle measuring instrument (DropMaster manufactured by Kyowa Interface Science Co., Ltd.) was used. The contact angle 1 second after dropping 2 μL of water droplets onto the adhesive surface of the protective film was measured according to the fitting method (Height Width Automatic method (θ / 2 method)). The average value of N = 3 was taken as the average contact angle with water.

[0252] (2) Average Contact Angle of the Adhesive Surface of the Protective Film with Hexadecane

[0253] For the protective film before being adhered to the hard coat, the contact angle of its adhesive surface with hexadecane was measured. When measuring, a contact angle measuring instrument (DropMaster manufactured by Kyowa Interface Science Co., Ltd.) was used. The contact angle 1 second after dropping 2 μL of hexadecane (C 16 H 34 ) droplets onto the adhesive surface of the protective film was measured according to the fitting method (Height Width Automatic method (θ / 2 method)). The average value of N = 3 was taken as the average contact angle with hexadecane.

[0254] (3) Surface Free Energy of the Adhesive Surface of the Protective Film

[0255] Based on the obtained average contact angle values with water and hexadecane, the surface free energy value was calculated according to the Kaelble-Uy method.

[0256] (4) Nanoindentation hardness of uncured hard coating

[0257] Using a ultra-microindentation hardness testing device (ENT-NEXUS manufactured by Elionix), under the following conditions, the nanoindentation hardness of the cross-section in the thickness direction of the uncured hard coating obtained in the examples and comparative examples was measured. The measurement position was set at the central part of the hard coating, and the average value of the measurement values of 25 points near the center in the thickness direction of the central part was taken as the indentation hardness (N / mm 2 ).

[0258] Indenter: Berkovich indenter (opposite vertex angle 65.03°),

[0259] Surface detection: The loading load was set (0.5 mN) so that the displacement amount was 1 / 10 of the hard coating,

[0260] Loading curve: 10 seconds, 0.5 mN (linear),

[0261] Holding time: 5 seconds, 0.5 mN,

[0262] Unloading curve: 10 seconds, 0 mN (linear),

[0263] Set temperature: 30 °C,

[0264] Device setting environment: 23 °C, 50% RH.

[0265] Using the above measurement results, according to the calculation based on ISO14577-1 2002-10-01 Part1 (calculated by the built-in software of the device), the nanoindentation hardness was calculated.

[0266] In addition, since the hardness of the specimen changes due to the influence of moisture absorption, the measurement was carried out after standing in an environment of 23 °C and 50% RH for more than 24 hours.

[0267] (5) SW hardness (scratch resistance) of cured hard coating

[0268] First, the protective film was removed from the thermoformed laminate made in the examples and comparative examples. Then, the hard coating of the thermoformed laminate obtained in the examples and comparative examples was irradiated with ultraviolet light to cure the hard coating. Using a conveyor belt type UV irradiator ECS-401GX manufactured by iGraphic, ultraviolet irradiation was carried out under the conditions of 700 mj / cm 2 (measurement wavelength 360 nm, high-pressure mercury lamp).

[0269] On the surface of the resulting cured hard coat, the hard coat was scratched 15 times back and forth with #0000 steel wool under a pressure of 100 gf / cm 2 . The haze values before and after scratching were measured with a haze meter (HM-150 manufactured by Murakami Color Co., Ltd.) in accordance with JIS K 7136:2000. Then, the absolute value (ΔH) of the haze change before and after scratching was calculated. When the ΔH value was 3.0% or less, the scratch resistance was evaluated as good.

[0270] (6) Average contact angle of the cured hard coat with water

[0271] The contact angle of the cured hard coat with water was measured in the same manner as for the protective film, and the average value was similarly calculated.

[0272] (7) Average contact angle of the cured hard coat with hexadecane

[0273] The contact angle of the cured hard coat with hexadecane was measured in the same manner as for the protective film, and the average value was similarly calculated.

[0274] (8) Surface free energy of the cured hard coat

[0275] Based on the values of the average contact angles with water and hexadecane obtained above, the value of the surface free energy was calculated according to the Kaelble-Uy method.

[0276] (9) Fingerprint erasability of the cured hard coat

[0277] The back surface of the laminate after curing the hard coat was made black, and fingerprints were made to adhere to the surface of the hard coat. Then, the fingerprints were wiped off with a cloth, and the ease of fingerprint erasure was evaluated according to the following evaluation criteria.

[0278] A: The fingerprints disappeared after wiping 2 to 4 times.

[0279] B: The fingerprints disappeared after wiping 5 times.

[0280] C: The fingerprints disappeared after wiping 6 or more times.

[0281] The compositions and evaluation results of the thermoforming laminates related to the examples and comparative examples are shown together in Tables 2 and 3 below.

[0282] [Table 2]

[0283]

[0284] [Table 3]

[0285]

[0286] As can be seen from Table 2 and Table 3, the fingerprint erasability of the hard coating of the examples is excellent. It is considered that this fingerprint erasability is further improved by using a protective film having a specified surface free energy on the adhesion surface. In addition, particularly for the hard coatings of Examples 1 to 10, since the scratch resistance is also excellent, they are not easily damaged. These characteristics will be very beneficial in various products (such as home appliances, in-vehicle devices, automotive interior parts, etc.). In addition, particularly for the hard coatings of Examples 1 to 9 and 11, the nanoindentation hardness in the uncured state is high, so the operability in the uncured state is also excellent.

[0287] Although several embodiments of the present invention have been described, these embodiments are merely examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the gist of the invention. These embodiments and their modifications are not only included in the scope and gist of the invention but also included in the invention described in the claims and its equivalents.

[0288] Symbol Explanation

[0289] 10 Laminated body for thermoforming; 12 Protective film; 16 Hard coating; 20 Polymethyl methacrylate layer (substrate layer); 22 Polycarbonate layer (substrate layer).

Claims

1. A laminate for post-curing thermoforming, characterized in that: The laminate for post-curing thermoforming is formed by laminating a substrate layer, an uncured hard coat, and a protective film in sequence, After removing the protective film and curing the hard coating, the surface free energy of the surface of the hard coating is 20.0 mJ / m 2 Hereinafter, The surface free energy is calculated according to the values of the average contact angle with water and the average contact angle with hexadecane on the surface of the hard coat by the Kaelble-Uy method.

2. The laminate for post-curing thermoforming according to claim 1, characterized in that: Before being bonded to the hard coat, the adhesion surface of the protective film on the side of the hard coat has an average contact angle with water of 90° or more and an average contact angle with hexadecane of 8° or more.

3. The laminate for post-curing thermoforming according to claim 1 or 2, characterized in that: The hard coat contains a polymer having a (meth)acryloyl group and inorganic oxide nanoparticles, When the total of the polymer and the nanoparticles is set to 100 parts by weight, the content of the polymer having a (meth)acryloyl group in the hard coat is 40 to 99 parts by weight, and the content of the inorganic oxide nanoparticles is 1 to 60 parts by weight.

4. The laminate for post-curing thermoforming according to claim 3, characterized in that: The polymer having a (meth)acryloyl group has a (meth)acrylic acid equivalent of 200 to 700 g / eq, and the inorganic oxide nanoparticles have an average particle size of 5 to 300 nm.

5. The laminate for post-curing thermoforming according to claim 3 or 4, characterized in that: The hard coat further contains a leveling agent, When the total of the polymer and the nanoparticles contained in the uncured hard coat is set to 100 parts by weight, the content of the leveling agent is 0.001 to 10 parts by weight.

6. The laminate for post-curing thermoforming according to claim 5, characterized in that: The leveling agent is a fluorine-based additive.

7. The laminate for post-curing thermoforming according to claim 5 or 6, characterized in that: The hard coat further contains a light stabilizer, When the total of the polymer and the nanoparticles contained in the uncured hard coat is set to 100 parts by weight, the content of the light stabilizer is 0.1 to 10 parts by weight.

8. The laminate for post-curing thermoforming according to any one of claims 1 to 7, characterized in that: The nanoindentation hardness of the uncured hard coating at a temperature of 30 °C is 200 N / mm 2 or more.

9. The laminate for post-curing thermoforming according to any one of claims 1 to 8, characterized in that: After removing the protective film to cure the hard coat, when the surface of the hard coat was scratched 15 times reciprocally with steel wool under a pressure of 100 gf / cm 2 , the haze change ΔH before and after scratching of the hard coat was 3.0% or less. The haze change ΔH is evaluated according to JIS K 7136:2000.

10. The laminate for post-curing thermoforming according to any one of claims 1 to 9, characterized in that: The hard coat is an active energy ray-curable layer.

11. A molded article, characterized in that: The molded article is obtained by curing the uncured hard coat in a molding intermediate formed by molding the laminate for post-curing thermoforming according to any one of claims 1 to 10.

12. A method for manufacturing a molded body, characterized in that, Including: The step of thermoforming the laminate for post-curing thermoforming according to any one of claims 1 to 10; The step of removing the protective film from the post-cured thermoformed laminate for thermoforming obtained from the thermoforming; and The step of curing the hard coat layer exposed on the surface by removing the protective film.

13. The method for manufacturing a molded article according to claim 12, wherein: The thermoforming is performed by insert molding.

Citation Information

Patent Citations

  • Polycarbonate resin composition for light diffusion plate and light diffusion plate

    JP2007179018A

  • Hard coat containing an alkoxylated multi(meth)acrylate monomer and surface-treated nanoparticles

    JP2017508828A

  • Thermoforming laminate and method for molding laminate

    WO2021157588A1

  • Transfer film for in-mold molding, method for producing in-mold molded body, and molded body

    CN104870185A

  • Method for manufacturing touch panel, touch panel, method for manufacturing molded article, molded article, and laminated film

    CN105027045A